BUILDING INTERACTIVE INTERACTIONS IN ENGLISH TEACHING BY USING PICTURES - Firmansyah Diyata (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
One way to build interaction between the teacher and the students or among students is by pictures. Through the pictures that are shown by the teacher, students are able to be encouraged to say words or sentences in English. In an interactive teaching process, teacher can use the pictures to invite students’ opinions through the lead-in questions before the activity, discuss the context he creates during the stages of presentation, practice and production, and let the students express their thoughts after they join each stage of the lesson. All those interaction activities create interactions that build communication that help students to produce sentences based on the target language they need to acquire in every lesson topic they join.